Processo markoviano de decisão para alocação dinâmica de recursos e controle de admissão de conexão em redes IEEE 802.16 - LEAL, Cynthia Feitosa (Universidade Federal do Pará, 2012)
This work presents a solution to the problem of connection admission control and dynamic resource allocation in IEEE 802.16 networks by modeling a Markov Decision Process (MDP) using the concept of bandwidth degradation, which is based on different bandwidth requirements of IEEE 802.16 service classes. In oder to test the performance of the MDP, different returns for each class of service are allocated, thus making the differential treatment of each service classes. Therefore, it is possible to evaluate the optimal policy, obtained through a value iteration algorithm, considering aspects such as the service classes average adjustment, resource utilization and blocking probability in relation to system load. Results obtained show that the Markov control method proposed is able to prioritize service classes considered most relevant to the system.